Matrix metalloproteinase-2 knockout prevents angiotensin II-induced vascular injury. Issue 14 (20th July 2017) - Barhoumi, Tlili; Fraulob-Aquino, Julio C; Mian, Muhammad Oneeb Rehman; Ouerd, Sofiane; Idris-Khodja, Noureddine; Huo, Ku-Geng; Rehman, Asia; Caillon, Antoine; Dancose-Giambattisto, Bianca; Ebrahimian, Talin; Lehoux, Stéphanie; Paradis, Pierre; et al.
Abstract: Aims: Matrix metalloproteinases (MMPs) have been implicated in the development of hypertension in animal models and humans. Mmp2 deletion did not change Ang II-induced blood pressure (BP) rise. However, whether Mmp2 knockout affects angiotensin (Ang) II-induced vascular injury has not been tested. We sought to determine whether Mmp2 knockout will prevent Ang II-induced vascular injury. Methods and results: A fourteen-day Ang II infusion (1000 ng/kg/min, SC) increased systolic BP, decreased vasodilatory responses to acetylcholine, induced mesenteric artery (MA) hypertrophic remodelling, and enhanced MA stiffness in wild-type (WT) mice. Ang II enhanced aortic media and perivascular reactive oxygen species generation, aortic vascular cell adhesion molecule-1 and monocyte chemotactic protein-1 expression, perivascular monocyte/macrophage and T cell infiltration, and the fraction of spleen activated CD4 + CD69 + and CD8 + CD69 + T cells, and Ly-6C hi monocytes. Study of intracellular signalling showed that Ang II increased phosphorylation of epidermal growth factor receptor and extracellular-signal-regulated kinase 1/2 in vascular smooth muscle cells isolated from WT mice. All these effects were reduced or prevented by Mmp2 knockout, except for systolic BP elevation. Ang II increased Mmp2 expression in immune cells infiltrating the aorta and perivascular fat. Bone marrow (BM) transplantation experiments revealed that in absence of MMP2 in immune cells, Ang II-induced BP elevation was decreased, and that when MMP2 was deficient in either immune or vascular cells, Ang II-induced endothelial dysfunction was blunted. Conclusions: Mmp2 knockout impaired Ang II-induced vascular injury but not BP elevation. BM transplantation revealed a role for immune cells in Ang II-induced BP elevation, and for both vascular and immune cell MMP2 in Ang II-induced endothelial dysfunction.